2002
DOI: 10.1111/j.1460-2466.2002.tb02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Young Females' Images of Motherhood in Relation to Television Viewing

Abstract: This study explored the relationship between television viewing and young females' images of motherhood. The respondents were 166 Dutch adolescents (age 15-17) and young women (age 20-22) with various educational backgrounds. None were mothers. We examined the young females' self-image and ideal image of motherhood and explored the extent to which television viewing and viewing motives were related to these images. It was not the total amount of television exposure, but the exposure to certain sitcoms and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…It is important to remember that although these plans may be sharpened in college, students have been surrounded by idealized images of the breadwinner-caregiver model throughout childhood (Ex et al 2002;Smith et al 2010). Additionally, they have created templates for their future roles by observing their parents, who typically also divided labor in a gendered way (Fulcher et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…It is important to remember that although these plans may be sharpened in college, students have been surrounded by idealized images of the breadwinner-caregiver model throughout childhood (Ex et al 2002;Smith et al 2010). Additionally, they have created templates for their future roles by observing their parents, who typically also divided labor in a gendered way (Fulcher et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Researchers addressing these issues often argue in favor of genre-specific effects. In a study of female adolescents and young adults in Holland, Ex, Janssens, and Korzilius (2002) found that exposure to sitcoms and soaps (but not overall amount of viewing) predicted anticipating a traditional motherhood, in which they would be devoted to family and children rather than focused on the world outside the home. Segrin and Nabi's (2002) study of 285 university students found that while overall amount of viewing was related to holding less idealistic expectations regarding romance and marriage, those who watch more ''romantic'' programs express more idealistic and romanticized views; they also wish to get married at a younger age, and believe that ''my marriage will last forever,'' etc.…”
Section: Other Recent Findingsmentioning
confidence: 98%
“…Previous research found that young women’s heavy exposure to programs featuring traditional mothers was linked with more gender traditional beliefs about motherhood (Ex et al, 2002). Similarly, we found that more exposure to programs featuring fathers was linked with less egalitarian family gender role beliefs in both women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Survey data indicate that both general TV exposure and viewing of specific genre types (e.g., domestic comedies) are associated with children’s and adults’ beliefs about family behavior, such as conflict and support (Alexander, 2009; Buerkel-Rothfuss, Greenberg, Atkin, & Neuendorf, 1982; Signorielli, 1989; Wilson, 2004). In a study of adolescent girls’ and undergraduate women’s exposure to sitcoms and soap operas, greater consumption of TV series that depicted traditional mothers was associated with a more traditional view of motherhood (Ex, Janssens, & Korzilius, 2002). This study also examined viewing motivations and found that women and girls who watched TV out of habit rather than for learning purposes endorsed more traditional views of motherhood.…”
Section: Shaping Of Family Beliefs Through Tvmentioning
confidence: 99%
See 1 more Smart Citation